Evaluation of Functional Bread From Wheat, Yellow Corn, African Catfish, Mackerel, and Red Crayfish Flour Blends - Anna Ngozi Agiriga; Maduebibisi Ofo Iwe; Sofiat Abiodun Ajani; Rofihat Tolase Oyewole; Mabel Mosunmola Akinola (Food ScienTech Journal, 2026)
Consumers’ awareness of the need to eat functional foods is increasing. Functional bread was produced from wheat, yellow corn, African catfish, mackerel fish, and red crayfish. 100% wheat flour (WF100) was the control. Ten bread samples were formulated: a control (100% wheat flour, SWF100) and nine composite variations with increasing substitution levels of yellow corn, African catfish, mackerel fish, and red crayfish flours. Functional properties of the flour samples were determined. Proximate, physical, and sensory properties of the bread samples were evaluated. The water absorption capacity of the blends ranged between 1.30 to 1.58 g/ml, oil absorption capacity, 1.01 to 1.50 g/ml; bulk density, 0.41 to 0.54 g/cm3; foaming capacity, 3.43% to 4.13%; and solubility, 14.45% to 18.33%. The protein content of the bread samples ranged between 12.83% to 17.91%; fat, 1.60% to 7.33%; ash, 1.53% to 3.87%; fibre, 0.35% to 0.49%; and carbohydrates, 43.57% to 54.98%. The weight of the bread samples ranged from 221.37 to 247.90 g, Height, 3.13 to 3.90 cm; volume, 508.76 to 812.02 cm3, and specific volume, 2.14 to 3.67 cm3/g.  SWF100 had the lowest value in all the nutritional attributes analyzed, but the highest carbohydrate content. The functional bread samples compared favorably with SWF100 in all the sensory attributes assessed. Bread samples from wheat (90%), yellow corn (5%), and mackerel fish (5%) (SWYM90:5:5), were the most acceptable with an acceptability score of 7.80 and compared favorably with SWF100 with an acceptability score of 7.85. The functional breads offer a nutritious alternative to wheat bread.